Function of Macrophage and Parasite Phosphatases in Leishmaniasis - Soulat, Didier; Bogdan, Christian (Frontiers in Immunology, 2017)
The kinetoplastid protozoan parasites belonging to the genus Leishmania are the causative agents of different clinical forms of leishmaniasis, a vector-borne infectious disease with worldwide prevalence. The protective host immune response against Leishmania parasites relies on myeloid cells such as dendritic cells and macrophages in which upon stimulation by cytokines (e.g. interferon [IFN]-gamma) a complex network of signaling pathways is switched on leading to strong antimicrobial activities directed against the intracellular parasite stage. The regulation of these pathways classically depends on post-translational modifications of proteins, with phosphorylation events playing a cardinal role. Leishmania parasites can deactivate their phagocytic host cells by inducing specific mammalian phosphatases that are capable to impede signaling. On the other hand, there is now also evidence that Leishmania spp. themselves can express phosphatases that might target host cell molecules and thereby facilitate the intracellular survival of the parasite. This review will present an overview on the modulation of host phosphatases by Leishmania parasites as well as on the known families of Leishmania phosphatases and their possible function as virulence factors. A more detailed understanding of the role of phosphatases in Leishmania-host cell interactions might open new avenues for the treatment of non-healing, progressive forms of leishmaniasis.